2016
DOI: 10.1007/s00192-016-3185-3
|View full text |Cite
|
Sign up to set email alerts
|

Coital incontinence: a factor for deteriorated health-related quality of life and sexual function in women with urodynamic stress urinary incontinence

Abstract: Introduction and hypothesisTo assess the impact of coital incontinence (CI) on health-related quality of life (HRQoL) and quality of sexual function (QSF) in women with urodynamic stress urinary incontinence (SUI).MethodsWomen were recruited for this cross-sectional study from among 289 patients with lower urinary tract symptoms, underwent clinical and urodynamic evaluation. Of these 289 women, 127 sexually active women with SUI completed the King’s Health Questionnaire (KHQ) and the Pelvic Organ Prolapse/Urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Studies have been determined that increase in UI severity negatively affected the quality and frequency of sexual intercourse. It was also reported that women who had sexual incontinence had lower quality of life than women who did not 27‐29 . In studies conducted in Turkey, it is determined that feeling ashamed of incontinence was due to the smell or wet feeling, adversely affecting sex life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been determined that increase in UI severity negatively affected the quality and frequency of sexual intercourse. It was also reported that women who had sexual incontinence had lower quality of life than women who did not 27‐29 . In studies conducted in Turkey, it is determined that feeling ashamed of incontinence was due to the smell or wet feeling, adversely affecting sex life.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, women with UI with concomitant coital UI negatively experience this specific symptom, which has an influence in different dimensions of the quality of life [24,25] (e.g., emotional, relational and sexual). In relation to this, Illiano et al [18] showed that coital UI was associated with increased severity of UI according to the ICIQ-SF scores, as well as with higher impact on the quality and frequency of sexual activity.…”
Section: Urinary Incontinence During Sexual Activitymentioning
confidence: 99%
“…[16][17][18][19] Stress urinary incontinence is strongly involved in urinary incontinence during sexual intercourse, with reduced urethral resistance contributing the most. [20][21][22][23] In surgery for stress urinary incontinence and pelvic organ prolapse, it has been reported that, while it improves sexual function, there is apprehension that transvaginal mesh implantation can cause dyspareunia (coital pain) and chronic pain. [24][25][26][27][28][29][30] CQ11.…”
Section: Selected Cqsmentioning
confidence: 99%